Understanding youth political demand based on demographic patterns in Malaysia: An overview of parochialism and development in the Sabah state election, 2020 - Adi Jafar; Zaini Othman; Nordin Sakke; Ramli Dollah; Eko Prayitno Joko; Md Saffie Abdul Rahim (Allied Academies, 2021)
Youths are also the largest group of voters in Malaysia and Sabah in particular. This demonstrates that the youth plays a vital role in determining the victory of a party. Therefore, understanding the needs of youth voters will give an advantage to a political party in the election situation. Therefore, this study seeks to identify the political demands of youth voters in Sabah from development and parochialism perspectives based on the zones and parliamentary boundaries. Furthermore, this research aims to determine the impact of youth voters' demographic backgrounds on their political demands. This study involved a total of 1,609 youth voters throughout Sabah. The raw data were then analyzed using the Principal Component Analysis (PCA) techniques presented in thematic maps using the Geography Informatics System (GIS) application. This study found that there are generally five primary political demands of youth voters in Sabah based on priorities: stability of the state, space for political involvement, anti-racist caliber leaders, territorial equality rights, and the provision of welfare assistance. However, priorities of political demands in every zone and parliaments in Sabah varied due to the diverse demographic background of the constituents.